Seeing and managing rock art at Nganjarli: A tourist destination in Murujuga National Park, Western Australia. Issue 3 (2nd September 2021) - McDonald, Jo; Mulvaney, Ken; Beckett, Emma; Fairweather, John; Morrison, Patrick; de Koning, Sarah; Dortch, Joe; Jeffries, Peter
Abstract: The Nganjarli site complex, which includes a rich body of rock art, shell middens and artefact scatters, has been identified by the Murujuga Aboriginal Corporation (MAC) as the primary location within Murujuga National Park for tourism and interpretation facilities. Murujuga National Park lies on the north-west coast of Western Australia, and within the Dampier Archipelago (including Burrup Peninsula) National Heritage Place. MAC owns and co-manages the National Park with the Department of Biodiversity Conservation and Attractions. Facilities have been upgraded to accommodate increasing tourist numbers and enhance their cultural experience at Nganjarli. Archaeological evidence was documented ahead of the installation of a boardwalk and concrete walking trails for viewing rock art. The national heritage values of this place are demonstrated, and we outline how existing co-management has mobilised contemporary cultural values and the aspirations of the Murujuga custodians. We document the role of innovative scientific approaches in the interpretive strategy for Nganjarli. New recording techniques and digital imaging demonstrate the diversity of animal motifs in the rock art near the installed boardwalk and identify opportunities for further digital interpretation of this significant landscape. Geochemical testing of surface lithic artefacts using X-ray fluorescence indicates mixed sourcing in the preferred lithics despite this being a tool-stone rich environment. Surface shell derives from targeted harvesting of a single species. The combined archaeological evidence indicates that Nganjarli has functioned as an aggregation locale through time. The rock art assemblage indicates that occupation here began during the earlier phases of art production. All these findings have been incorporated into the interpretative facilities in the tourist area.